Ectopic nasal tooth associated with cleft lip and palate - Subhransu Basu; Sudipto Sahu; Abhinaba Bose; Sucharu Ghosh (Wolters Kluwer Medknow Publications, 2021)
Ectopic nasal tooth is a rare phenomenon with only 0.1%-1% incidence rate. They are more frequently found coupled with cleft lip and palate. Here, we present a case of intranasal tooth in a 12-year-old male child with operated cleft lip and palate. The condition was diagnosed only on the basis of intraoral periapical radiograph and was extracted using gauge-holding forceps at a rural health-care center. We discuss the possible etiology, clinical findings, diagnosis, and treatment modalities of this condition. The purpose of this paper is to highlight that this rare condition can be managed with minimum available equipment in a rural setup.